A new species of Ainudrilus (Tubiﬁcidae) from South Georgia, and other subantarctic freshwater oligochaetes. - Erséus, C.; Grimm, R. (Hydrobiologia, 2002)
The freshwater oligochaetes of the subantarctic islands are reviewed and new records are given. Ainudrilus dartnalli sp.n. (subfamily Rhyacodrilinae) is described from freshwater sites on South Georgia (South Atlantic Ocean). It differs from the closely related, southwest Australian, A. nharna Pinder & Brinkhurst, by its longer clitellum, the longer upper teeth of its ventral somatic chaetae, its straighter and fewer penial chaetae, and by the proportions of its spermathecae. Range extensions are given for two widespread naidids, Nais variabilis Piguet and N. communis Piguet, from the Falkland Islands (S. Atlantic). Moreover, new material of N. elinguis Müller is recorded from Macquarie Island (Southern Ocean, SW of New Zealand).